2011
DOI: 10.1093/nar/gkr578
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine methylation alters DNA mechanical properties

Abstract: DNA methylation plays an essential role in transcriptional control of organismal development in epigenetics, from turning off a specific gene to inactivation of entire chromosomes. While the biological function of DNA methylation is becoming increasingly clear, the mechanism of methylation-induced gene regulation is still poorly understood. Through single-molecule force experiments and simulation we investigated the effects of methylation on strand separation of DNA, a crucial step in gene expression. Molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
128
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(142 citation statements)
references
References 72 publications
14
128
0
Order By: Relevance
“…Nevertheless, irregular conformations were seen quite commonly in vivo in studies by electron and optical microscopy (for example [31,32]) ( Figure 3B) and were also predicted by simulation of the response to crowding of linear polyelectrolyte polymers [9,33] (Figure 3A) and by considering that chromosomes resemble block copolymers [34,35] with interspersed regions of repeated DNA sequences [36], methylated cytosine-containing DNA which has particular conformational properties [37,38], and nucleosomes containing variant or modified histones which influence fiber interactions [39,40]. These discrepancies have been resolved by recent cryo-electron microscopy and X-ray scattering studies, which show conclusively that chromatin fibers exist in vivo in a disordered, interdigitated state resembling a polymer melt [41].…”
Section: Structure and Packing Of Chromosomes Chromatin Fibersmentioning
confidence: 59%
“…Nevertheless, irregular conformations were seen quite commonly in vivo in studies by electron and optical microscopy (for example [31,32]) ( Figure 3B) and were also predicted by simulation of the response to crowding of linear polyelectrolyte polymers [9,33] (Figure 3A) and by considering that chromosomes resemble block copolymers [34,35] with interspersed regions of repeated DNA sequences [36], methylated cytosine-containing DNA which has particular conformational properties [37,38], and nucleosomes containing variant or modified histones which influence fiber interactions [39,40]. These discrepancies have been resolved by recent cryo-electron microscopy and X-ray scattering studies, which show conclusively that chromatin fibers exist in vivo in a disordered, interdigitated state resembling a polymer melt [41].…”
Section: Structure and Packing Of Chromosomes Chromatin Fibersmentioning
confidence: 59%
“…It is not known whether there are any DNA-binding proteins in E. coli with transcriptional regulatory roles whose activities are dependent on the methylation state of the substrate DNA. However, cytosine methylation also alters the mechanical properties of DNA 52 , and this might have profound consequences on transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Bianchi & Zangi explored the impact of cytosine methylation on base flipping [63], and the mechanisms of recognition by proteins of DNA containing MeC [97]. Broyde and coworkers used QM/MM to explore basic structural properties of DNA containing MeC [98], and Carvalho and coworkers [99] confirmed previous claims by other authors [100,101] that methylation largely alters the elastic properties of DNA. These studies suggested that methylation-related changes might affect the nucleosome binding, a hypothesis that has been confirmed in recent studies [102,103].…”
Section: Atomistic Studiesmentioning
confidence: 65%